Redox aspects of lithium-ion batteries - Peljo, Pekka; Villevieille, Claire; Girault, Hubert H. (Royal Society of Chemistry (RSC), 2025)
This article aims to present the redox aspects of lithium-ion batteries both from a thermodynamic and from a conductivity viewpoint. We first recall the basic definitions of the electrochemical potential of the electron, and of the Fermi level for a redox couple in solutions. The Fermi level of redox solids such as metal oxide particles is then discussed, and a Nernst equation is derived for two ideal systems, namely an ideally homogenous phase where the oxidised and reduced metal ions are homogeneously distributed and two segregated phases where the oxidised and the reduced metal ions are separated in two distinct phases such as observed, for example, in biphasic lithium iron phosphate. The two different Nernst equations are then used to explain the difference in conductivity, the former being more conductive due to redox conductivity.